PENYEBAB IKAN BERCITA RASA LUMPUR DAN PENANGANANNYA UNTUK KONSUMSI - M. Nasyiruddin Arsyad (University of PGRI Palembang, 2004)
Fish and shrimp lived in bloomed of blue green algae environment commonly face muddy flavour problem. That was cased by geosmin, a metabolite product of blue green algae. It can be found in pounds, both in freshwater or brachiswater,and in open water area. Geosmin absorbed by fish through the gill, skin, intestine and stomach. The concentration of geosmin in fish or shrimp according to be concertation in the environtmen and the length of time of fish or shrimp in such environment. Among several methods to reduce or eliminate this muddy flavour, physical method is the mostly applied by fish farmer or fish saler. In addition to fish processing method is another way to solve the muddy flavour in fish.Keywords: fish, blooming algae, geosmin, physical method